Analisis Pengaruh Waktu Tunggu dan Mutu Pelayanan Farmasi Terhadap Kepuasan Pasien di Puskesmas Citeureup - Riyanto, Agus; Megasari, Mona (Jurnal Kesehatan Rajawali, 2025)
Patient satisfaction is the level of patient feelings that arise from the results of health service performance obtained after the patient compares the services he receives. Patient satisfaction is influenced by aspects of pharmaceutical services such as drugs, attitudes and services of pharmaceutical personnel, comfort and cleanliness of the waiting room and waiting time for drugs. This study purpose was to determine the effect of waiting time and quality of pharmaceutical services on patient satisfaction at the Citeureup Public Health Center. This study used cross sectional design. The research sample was 101 patients at the Citeureup Public Health Center. Data collection using a questionnaire and data analysis was using the chi-square test. Results of the study showed that there was an influence of waiting time and quality of pharmaceutical services on patient satisfaction (p= 0.009 and p= 0.001). Pharmaceutical installation officers must be friendly and clear in conveying information to improve the quality of service and be able to meet the expectations and needs of patients.